Quantitation and karyometry of cerebral neuroglia and endothelial cells in liver cirrhosis and in the hepatosplenic schistosomiasis mansoni - Brasileiro-Filho, G.; Guimaraes, R. C. [UNESP]; Pittella, J. E.H. (Springer Nature, 1989)
A morphological, karyometric, and quantitative study of cerebral neuroglia and endothelial cells of blood capillaries was done in cirrhotic and in hepatosplenic schistosomotic human autopsied cases. Cluster analysis applied to them revealed three subgroups (cirrhosis and schistosomiasis polar groups and one intermediate). The comparison of these three groups with a control revealed increased numbers of astrocytes, oligodendrocytes and endothelial cells, but no nuclear enlargement in the schistosomiasis group; the cirrhosis group exhibited a pronounced nuclear enlargement of both astrocyte and oligodendrocytes but no increase in cell numbers. The intermediate group, which encompasses the majority of pathological cases, is heterogeneous but on average behave as the cirrhosis group in that nuclear enlargement, but no increase in cell numbers, was noted. Such changes could represent a response of the nervous system to the metabolic disturbances present in hepatic and/or portal-systemic encephalopathy. There was a positive correlation between glial and endothelial cell numbers in cerebral cortex, suggesting a functional relationship between the glial cells and the capillary bed. This study points out the importance of clustering the cases, because the physiopathological status of individuals belonging to the same nosological condition can be different. Comparisons considering this aspect should be useful in understanding the progression of the pathological process. © 1989 Springer-Verlag.
Keywords: Cell number; Glial cells; Kariometry; Liver cirrhosis; Schistosomiasis